2019
DOI: 10.1111/vde.12726
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral collagen index predicts mortality and survival in canine cutaneous mast cell tumours

Abstract: Background -Mast cell tumours (MCTs) constitute almost 25% of cutaneous neoplasms in dogs. Their biological behaviour is predicted using histopathological grading which is based on several subjective criteria that are vulnerable to intra-and interobserver variability. To improve the prediction of the biological behaviour, several complementary markers have been studied. The integrity of the extracellular matrix (ECM) may play a protective role against tumoral progression, and favour cellular proliferation, ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…One of the advantages of using MT staining is its low-cost and practical implementation compared to other techniques. It has been observed that higher intratumoral collagen levels are associated with lower-grade canine cutaneous mast cell tumors, with greater survival times in those with a value lower than 9.25% [29,32]. In female dogs with mammary tumors, aggressive carcinomas with shorter collagen fibers are present, which directly affects the survival time [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the advantages of using MT staining is its low-cost and practical implementation compared to other techniques. It has been observed that higher intratumoral collagen levels are associated with lower-grade canine cutaneous mast cell tumors, with greater survival times in those with a value lower than 9.25% [29,32]. In female dogs with mammary tumors, aggressive carcinomas with shorter collagen fibers are present, which directly affects the survival time [34].…”
Section: Discussionmentioning
confidence: 99%
“…Masson's trichrome (MT) staining is a low-cost, practical method used for assessing the ECM, which is a major component of the tumor microenvironment. High intratumoral collagen levels have been associated with increased survival time in dogs with low-grade cutaneous mast cell tumors [29,32]. Compounds that inhibit the adhesion of tumor cells to the ECM have also been shown to prevent metastasis [33].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the ICI was not an efficient prognostic marker for canine OMs. Despite the fact that density and alignment of the collagen fibers are considered prognostic markers for human breast cancer, [26][27][28] and that the ICI is an indicator of mortality and postsurgical survival for canine cutaneous mast cell tumors, 31 the values obtained for OMs were very low and similar between lesions. The source of the tumors included in the present study, specialized oncology and dentistry services, might have influenced our results, perhaps selecting for cases of higher malignancy and, consequently, melanocytic tumors with higher cellularity and less stroma.…”
Section: Discussionmentioning
confidence: 99%
“…20,26,27 Additional studies have elucidated other ECM roles in tumor invasion and metastasis. 22,[28][29][30][31] Invasion and metastasis formation depend on enzymatic degradation, especially by matrix metalloproteinases, whose expression is also influenced by ECM members. 20,22,29 Compounds that inhibit tumor cell adhesion to the ECM are capable of preventing metastases, demonstrating the importance of studies to characterize ECM alterations in cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation